PENGARUH BRAIN GYM TERHADAP KONSENTRASI ANAK USIA 7-8 TAHIN DI SD MUHAMMADIYAH 04 DEPOK - Regiana Aisya Romadhon (2022)
Background: Investment from a country, namely in school-age children. The quality of today's children will determine the quality of tomorrow's country. To determine the quality that is influenced by the acquisition of children's concentration in the teaching and learning process. Exercising at the Brain Gym is also to pass on a good effect in developing focus, attention, alertness to determine the conditions. In the pattern of learning at the Brain Gym regardless of age and gender. Focus is the duration of thoughts that occur by themselves in everyone. To turn on the physical sensation, it takes a period of quiet time as well as a happy mood. Because when the atmosphere is full of pressure or burden, the individual is not able to function his brain and mind optimally and his thoughts become chaotic. In the second stage of education, namely Elementary School. Purpose: This study was to block the effects of giving Brain Gym equipment on the concentration of children aged 7-8 years at SD Muhammadiyah 04 Depok. Methods: In this study, a color guessing instrument was used to determine the level of focus of a student. determine the pre-experimental and the form of each group in the form of one group can be called Pretest-Posttest. The respondents used were students of grade 2 SD Muhammadiyah 04 Depok aged 7-8 years, totaling 60 samples. Results: of data analysis determine the Kolmogorov Smirnov test. The results of the Paired Sample T-test prove that there is no effect of giving with the Brain Gym tool on the memory of children aged 7-8 years with a score of 0.344 which means (0.344 > 0.05) so the results are declared insignificant.